Energy Efficient Thermal Management of Data Centers - Joshi, Yogendra; Kumar, Pramod (Springer New York : Imprint: Springer, 2012)
Energy Efficient Thermal Management of Data Centers examines energy flow in today's data centers. Particular focus is given to the state-of-the-art thermal management and thermal design approaches now being implemented across the multiple length scales involved. The impact of future trends in information technology hardware, and emerging software paradigms such as cloud computing and virtualization, on thermal management are also addressed. The book explores computational and experimental characterization approaches for determining temperature and air flow patterns within data centers. Thermodynamic analyses using the second law to improve energy efficiency are introduced and used in proposing improvements in cooling methodologies. Reduced-order modeling and robust multi-objective design of next generation data centers are discussed. This book also: Provides in-depth treatment of energy efficiency ideas based on  fundamental heat transfer, fluid mechanics, thermodynamics, controls, and computer science Focuses on multiple broad approaches that can yield significant improvements in data center energy efficiency Contains comprehensive coverage of all aspects of thermal management in data centers Features an introduction to real-time allocation of computing loads in virtualized environments and cloud computing Energy Efficient Thermal Management of Data Centers is an essential book for academic researchers working in thermal design, power delivery and cloud computing, as well as engineers working in critical facility design,cooling equipment and IT manufacturing.